Prevalence of calcified carotid artery on panoramic radiographs in postmenopausal women - Jamileh Beigom Taheri; Mahkameh Moshfeghi (Tabriz University of Medical Sciences, 2009)
Background and aims. This study was designed to evaluate the prevalence of calcified carotid artery in 50 year-old and older postmenopausal dental outpatients for early diagnosis of individuals at risk of stroke.
Materials and methods. This is a descriptive study of 200 panoramic radiographs. These radiographs included postmenopausal women referring to the Department of Oral Medicine at Shahid Beheshti Faculty of Dentistry during 2006-2007. The x-ray machine, developer and film type were the same for all the radiographs. Statistical analysis included chi-square test and Fisher's exact test.
Results. We found 22 calcified carotid arteries. The left and right carotid arteries were involved in 7 and 9 cases, respectively. In 6 cases both carotid arteries were calcified. Four individuals had no vascular risk factor excluding age and others had at least one risk factor. We found significant statistical correlation between hypertension, past history of myocardial infarction, and hypercholesterolemia with calcified carotid artery on panoramic radiographs.
Conclusion. Under the limitations of the present study, prevalence of calcified carotid arteries is 11.0 % in 50 year-old and older postmenopausal dental outpatients.